Health care workers’ qualitative descriptions of ethically challenging situations evoking moral distress during Covid-19 - Glad, Kristin Alve (Nursing ethics, 2024)
BackgroundThe high public demand for healthcare services during the COVID-19 pandemic and strict infection control measures, coupled with threat of severe illness and death, and limited resources, led to many healthcare workers (HCWs) experiencing ethically challenging situations (ECSs).ObjectiveTo systematically explore first-hand accounts of ECS-evoking moral distress among HCWs during this public health emergency.Research designThis was an open cohort study. All participants were asked whether they had been in ECS-evoking moral distress during the pandemic. Those who had were asked to describe these situations. Answers were systematically analyzed according to three levels of root causes for ECSs, using thematic analysis.Participants and research contextIn January 2022, 977 HCWs from four Norwegian university hospitals participated.Ethical considerationsThe study received ethical approval from the Norwegian Ethical Review Authority (No. 130944).ResultsIn total, 508 participants (52%) reported that they had experienced ECS-evoking moral distress during the pandemic, whereof 323 provided a qualitative description. We found that while a few reported ECSs caused at the patient level, and some described situations at the unit/team level, the vast majority reported situations caused at the system level, predominantly related to resource scarcity, particularly poor staffing.ConclusionOur findings strongly indicate that efforts to mitigate moral distress among HCWs should be targeted at the system level. More specifically, the study findings highlight resource limitations, particularly poor staffing, as a major cause of moral distress during the pandemic.